2017
DOI: 10.1016/j.resconrec.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Energy conservation and CO2 mitigation potentials in the Chinese pulp and paper industry

Abstract: China's paper production accounted for nearly a quarter of the world's total paper production in 2010. In this study, 23 energy saving technologies applicable to the pulping and papermaking process in China are identified and analyzed. The Conservation Supply Curve (CSC) method is employed to assess the technical and economic aspects of energy conservation. The fuel CSC forChinese pulp and paper industry shows the cost-effective and technical fuel conservation potential is 180 PJ and 254 PJ, accounting for 27%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…A large energy-saving potential in existing paper mills was also revealed by comparing operation data from 23 Dutch paper mills in the contribution presented by Laurijssen et al [18]. Another studies [19][20][21][22] analyzed the impact of potential energy savings in the pulp and paper industry considering emission reductions. Pulp and paper industry companies themselves have spent several hundred millions of investments to reduce the energy intensity of their plants in recent years [23].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A large energy-saving potential in existing paper mills was also revealed by comparing operation data from 23 Dutch paper mills in the contribution presented by Laurijssen et al [18]. Another studies [19][20][21][22] analyzed the impact of potential energy savings in the pulp and paper industry considering emission reductions. Pulp and paper industry companies themselves have spent several hundred millions of investments to reduce the energy intensity of their plants in recent years [23].…”
Section: Introductionmentioning
confidence: 89%
“…Constant improvement of energy efficiency in the pulping and papermaking processes was, indeed, a frequent subject of academic research with industrial applications [13][14][15][16][17][18][19][20][21][22]. Fleiter et al [13] provided a comprehensive overview of the options to improve energy efficiency in the German pulp and paper industry with the emphasis on possible future trends.…”
Section: Introductionmentioning
confidence: 99%
“…Energy conservation -efficiency of processes Laurijssen et al (2010) impact of different raw materials, in particular recycled fiber Hong et al (2011) evaluation of saving potential in production processes Chew et al (2013) brown stock washing system Utlu and Kincay (2013) examination of energy consumption between production processes Helin 2015scheduling of mechanical mass production with regards to energy prices Energy conservation -efficiency of technologies Fleiter et al (2012) technologies in processes and their impact to consumption Xu et al (2013) impact of technologies to consumption Lin and Moubarak (2014) evaluation of different scenarios to consumption Kong et al (2017) technical and economical aspect to consumption Energy conservation -national efficiency programs Stenqvist et al (2011) saving in terms of tax incentives Blomberg et al (2012) saving in terms of tax incentives Henriksson et al (2012) saving in terms of tax incentives Surveys, case studies, demand estimation, energy management in general Szabó et al (2009) simulation of consumption regarding different impact factors Thollander and Ottosson (2010) different energy management practices Ericsson et al (2011) climate policies, energy certificates Chen et al (2012) technology options, energy flow Comodi et al (2013) combined heat and power, comparison of plants Kong et al (2013) case study of energy auditing Machani et al (2013) profitability of bioenergy Ottosson and Magnusson (2013) policy measures, socio-technical destabilization…”
Section: (Ii) Environmentmentioning
confidence: 99%
“…Kong et al [64] identified and analysed 23 energy-saving technologies, 18 fuel-saving, and five electricity-saving technologies, applicable to the PPI in China. Furthermore, 25 emerging technologies for reduced energy use were reviewed after compiling available information such as energy use, costs, environmental benefits [47].…”
Section: Implementation Of Energy Efficiency Via Technologymentioning
confidence: 99%